Role of Lung Ultrasound for Diagnosis of Acute Respiratory Distress Syndrome in Intensive Care Unit - Afifa, Mayisha; Ahmed, Md Nasir Uddin; Ferdous, Mehnaz; Hossain, Md Mozaffer (Bangladesh Critical Care Journal, 2022)
Background: Acute respiratory distress syndrome (ARDS) necessitates rapid recognition for early intervention and favourable outcomes. The Berlin Definition may not be always helpful for ARDS diagnosis in critically ill patients, because of the inability to acquire adequate information from bedside chest X-rays. Lung ultrasound may be a reasonable alternative to chest X-ray for the identification of ARDS, but the effectiveness of lung ultrasound in ARDS diagnosis remains uncertain. Objective: To explore the efficacy of lung ultrasound (LUS) for the diagnosis of ARDS in ICU. Methods: This observational, cross-sectional study was conducted in the ICU, DMCH at the Department of Anaesthesia, Analgesia, Palliative, and Intensive Care Medicine from March 2017 to June 2019. Lung ultrasound was performed on acute hypoxic respiratory failure patients requiring mechanical ventilation. chest X-ray, arterial blood gas analysis, and echocardiography were done to fulfill the Berlin Definition. ARDS was diagnosed by the ‘CXR-based Berlin Definition’ and ‘LUS-based Berlin Definition’. Results: A total of 141 patients were assessed. Their median age was 35 years. Primary diagnoses were sepsis, pulmonary oedema, pneumonia, and trauma. A total of 62 (43.97%) patients fulfilled ‘CXR-based Berlin Definition’ and a total of 69 (48.93%) patients were diagnosed as ARDS by ‘LUS-based Berlin Definition’. Considering the ‘CXR-based Berlin Definition’ as the reference standard, the sensitivity, specificity, positive predictive value, negative predictive value, and accuracy of ‘LUS-based Berlin Definition’ were 90.3%, 83.5%, 81.2%, 91.7%, and 86.5% respectively. Conclusion: Lung ultrasound can be an effective tool for the diagnosis of ARDS in the intensive care unit. Bangladesh Crit Care J September 2022; 10(2): 104-109